Biocompatibility of plant extracts - Cury, Marina Tolomei Sandoval [UNESP]; Nunes, Gabriel Pereira [UNESP]; Vasques, Ana Maria Veiga [UNESP]; Almeida, Juliano Milanezi de [UNESP]; Matheus, Henrique Rinaldi [UNESP]; dos Reis-Prado, Alexandre Henrique; Dezan Junior, Eloi [UNESP]; Emerenciano Bueno, Carlos Roberto [UNESP] (My University, 2020)
Inflammation is an inner response of a host to an external agent, encompassing complex mediators and events. The use of antiinflammatory substances is applicable for the treatment of some conditions. The anti-inflammatory property of phytotherapics turns them into therapeutic option to conventional medicine and stimulates studies for use in humans. Herbals are widely used in popular medicine in many countries. However, the effectiveness of many of them remains poorly accessed. So, experimental researches aiming to investigate their pharmaceutical properties are essential to determine these paths and compatibility. This chapter will embrace experiments assessing the biocompatibility of extracts through cell culture, edema induction, subcutaneous tests and associations made with different extracts aiming to enhance the effectiveness of some compounds already used in daily practice. In addition, several promising plant extracts with scientifically proved results will be described.
Keywords: Biocompatibility; Ethnopharmacology; Inflammation; Phytotherapy; Plant Extracts